Variation in the Monoterpene Composition of Branch Cortical Oleoresin of Chir Pine - Raj, Anup; Sharma, K. R.; Sehgal, R. N. (Indian Forester, 2017)
Chir pine (Pinus roxburghii) is an important tree species that grows all along the Himalayas. A study was conducted to determine the monoterpene composition of cortical oleoresin in this species and also to find out if variation in its composition existed among twenty-two year old progenies of 58 plus trees of the species raised in a progeny test at Solan, Himachal Pradesh. Results of the study indicated that quantitative as well as qualitative variation in monoterpene composition of branch cortical oleoresin was present among the progenies. Five of the total 17 monoterpene compounds separated through gas chromatograph constituted more than 92% of the total monoterpenes. These were Î±-pinene, camphene, Î²-pinene, Î´3-carene and longifolene and they constituted 23.06, 10.72 1.80, 38.23 and 18.88 per cent of the 3 total monoterpene, respectively. Variation among progenies as revealed by CV value was highest for Î²pinene.